2019
DOI: 10.1007/s00227-019-3561-x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of reduced inorganic N:P ratio on three distinct plankton communities in the Humboldt upwelling system

Abstract: The ratio of inorganic nitrogen to phosphorus (NP) is projected to decrease in the Eastern Boundary Upwelling Systems (EBUS) due to warming of the surface waters. In an enclosure experiment, we employed two levels of inorganic NP ratios (10 and 5) for three distinct plankton communities collected along the coast of central Chile (33°S). The primary effect of the NP treatment was related to different concentrations of NO 3 , which directly influenced the biomass of phytoplankton. In addition, low inorganic NP r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Several recent studies have provided further evidence that changes in the N:P ratios of media (water or soil) or food affect the structure of food webs in terrestrial ecosystems (Fanin et al, 2013;Zechmeister-Bolstenstren et al, 2015;Paseka and Grunberg, 2019) and other studies have observed this link in aquatic ecosystems (Plum et al, 2015;Sitters et al, 2015;Lee et al, 2017;Zhao et al, 2018b;Nhu et al, 2019). Shifts in organismic stoichiometry throughout trophic webs due to changes in excreted stoichiometry and/or resource use (nutrients, light, water) have provided new insights into the changes in community composition, dynamics, and functionality in freshwater and marine ecosystems (Glibert et al, 2011;Hillebrand and Lehmpfuhl, 2011;Hessen et al, 2013;Plum et al, 2015;Galbraith and Martiny, 2015;Vanni and McIntyre, 2016;Filipiak, 2016;Moorthi et al, 2017;Vanderploeg et al, 2107;Branco et al 2018;Moody et al, 2018;Mousing et al, 2018;Prater et al, 2018;Spilling et al, 2019;Tanioka and Matsumoto, 2019). For example, the phenotypic selection of Synechococcus cyanobacteria living with a pathogenic phage was affected by the N:P stoichiometry of the medium, and thus, the associated co-evolutionary trophic pathways in the host-microbe community were affected because prey selection depends on the N:P ratios of the medium (Larsen, 2019).…”
Section: Effects Of Stoichiometry On Ecosystem Structure and Functionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several recent studies have provided further evidence that changes in the N:P ratios of media (water or soil) or food affect the structure of food webs in terrestrial ecosystems (Fanin et al, 2013;Zechmeister-Bolstenstren et al, 2015;Paseka and Grunberg, 2019) and other studies have observed this link in aquatic ecosystems (Plum et al, 2015;Sitters et al, 2015;Lee et al, 2017;Zhao et al, 2018b;Nhu et al, 2019). Shifts in organismic stoichiometry throughout trophic webs due to changes in excreted stoichiometry and/or resource use (nutrients, light, water) have provided new insights into the changes in community composition, dynamics, and functionality in freshwater and marine ecosystems (Glibert et al, 2011;Hillebrand and Lehmpfuhl, 2011;Hessen et al, 2013;Plum et al, 2015;Galbraith and Martiny, 2015;Vanni and McIntyre, 2016;Filipiak, 2016;Moorthi et al, 2017;Vanderploeg et al, 2107;Branco et al 2018;Moody et al, 2018;Mousing et al, 2018;Prater et al, 2018;Spilling et al, 2019;Tanioka and Matsumoto, 2019). For example, the phenotypic selection of Synechococcus cyanobacteria living with a pathogenic phage was affected by the N:P stoichiometry of the medium, and thus, the associated co-evolutionary trophic pathways in the host-microbe community were affected because prey selection depends on the N:P ratios of the medium (Larsen, 2019).…”
Section: Effects Of Stoichiometry On Ecosystem Structure and Functionmentioning
confidence: 94%
“…Several recent studies have provided information on how media (water or soil) or food C:N:P ratios affect the structure of food webs in freshwater (Hillebrand and Lehmpfuhl, 2011;Hessen et al, 2013;Filipiak, 2016;Moorthi et al, 2017;Prater et al, 2017;Vanderploeg et al, 2017;Wagner et al, 2017;Branco et al, 2018;Iannino et al, 2018;Moody et al, 2018;Prater et al, 2018;Zhang et al, 2018b;Bell et al, 2019) and marine ecosystems (Glibert et al, 2011;Galbraith et al, 2015;Bi et al, 2017;Branco et al, 2018;Mousing et al, 2018;Spilling et al, 2019;Tanioka and Matsumoto, 2019). The most intelligible advances, however, have been in terrestrial ecosystems, where conclusions were not possible earlier because of insufficient studies.…”
Section: Introductionmentioning
confidence: 99%
“…Yet it is surprising for such a strong driver of phytoplankton succession, like nitrate concentrations, that the deep water biology had such a measurable influence. A similar study in the southern (Chilean) Humboldt Current System investigated the impact of N:P ratios on different surface communities and came to the same conclusion: initial community composition was more important than inorganic N:P ratio for food web functioning and biogeochemistry (Spilling et al, 2019). Stable and consistent relationships between nutrient availability, consumption and the produced biomass are clearly not a feature of this dynamic ecosystem.…”
Section: Consequences For Phytoplankton Succession and Productivity A...mentioning
confidence: 82%
“…A decreasing inorganic N:P ratio resulting from reduced O 2 concentrations can be observed in different ecosystems. Short-term shifts are to some extent dependent on the plankton community composition (Spilling et al 2019, Bach et al 2020). However, potential long-term consequences of this phenomenon are little known.…”
Section: Discussionmentioning
confidence: 99%